Rapid restratification of the ocean surface boundary layer during the suppressed phase of the MJO in austral spring - Je-Yuan Hsu; Ming Feng; Susan Wijffels (Environmental Research Letters, 2022)
Rapid restratification of the ocean surface boundary layer in the Indonesian-Australian Basin was captured in austral spring 2018, under the conditions of low wind speed and clear sky during the suppressed phase of Madden–Julian Oscillations (MJOs). Despite sunny days, strong diurnal variations of sea surface temperature (SST) were not observed until the wind speed became extremely low, because the decreasing wind speed modulated the latent heat flux. Combined with the horizontal advection of ocean current, the reduced upward heat loss inhibited the nighttime convective mixing and facilitated the restratification of the subsurface ocean layers. The surface mixed layer was thus shoaled up to 40 m in two days. The restratified upper ocean then sustained high SSTs by trapping heat near the sea surface until the onset of the MJO convection. This restratification process might be initialized under the atmospheric downwelling conditions during the suppressed phase of MJOs. The resulted high SSTs may affect the development and trajectories of MJOs, by enhancing air-sea heat and moisture fluxes as the winds pick up. Simulating this detailed interaction between the near-surface ocean and atmospheric features of MJOs remains a challenge, but with sufficient vertical resolution and realistic initial conditions, several features of the observations can be well captured.